2003
DOI: 10.1038/sj.onc.1206781
|View full text |Cite
|
Sign up to set email alerts
|

The proto-oncoprotein c-Fos negatively regulates hepatocellular tumorigenesis

Abstract: Hepatocytes adopt an invasive and metastatic phenotype caused by the cooperation of transforming growth factor (TGF)-b and oncogenic Ha-Ras. In the initial phase of this process, c-Fos is rapidly induced by TGF-b, but then decreases to undetectable levels. Here, we investigated the functional implications of c-Fos activation and its contribution to hepatocellular tumorigenesis. By employing conditional c-Fos expression, we observed that continuous activation of c-Fos and consequently AP-1 activity leads to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 77 publications
2
55
2
Order By: Relevance
“…JUN can homodimerise to form the AP-1 transcription factor, which activates the expression of a number of genes involved in cell cycle regulation, including cyclin D1 (Albanese et al, 1995). However, an elevated cFos expression can also lead to apoptosis in hepatoma cells (Kalra and Kumar, 2004) and hepatocytes (Mikula et al, 2003). Furthermore, recent studies have shown that cFos transcriptionally represses the key antiapoptotic gene c-FLIP(L), greatly sensitising prostate cancer cells to TRAIL-induced apoptosis (Li et al, 2007;Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…JUN can homodimerise to form the AP-1 transcription factor, which activates the expression of a number of genes involved in cell cycle regulation, including cyclin D1 (Albanese et al, 1995). However, an elevated cFos expression can also lead to apoptosis in hepatoma cells (Kalra and Kumar, 2004) and hepatocytes (Mikula et al, 2003). Furthermore, recent studies have shown that cFos transcriptionally represses the key antiapoptotic gene c-FLIP(L), greatly sensitising prostate cancer cells to TRAIL-induced apoptosis (Li et al, 2007;Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of c-Fos results in apoptosis in murine hepatocytes that conditionally express c-Fos (Mikula et al, 2003). Fos À/À tp53 À/À double-knockout mice develop highly invasive and proliferative rhabdomyosarcoma, a tumour rarely observed in tp53 À/À knockout-mice (Fleischmann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of c-Fos was found to inhibit cell cycle progression, stimulated murine hepatocyte cell death and strongly suppressed tumour formation in vivo (Mikula et al, 2003). A functional involvement of c-Fos in apoptosis has been shown by its regulatory involvement during remodelling and stress response in various tissues in mouse development (Jochum et al, 2001).…”
mentioning
confidence: 99%
“…C-Jun and c-Fos are members of the AP-1 complex [12,15] . A number of studies found that COBRA1 may be associated with the AP-1 complex via physical binding to c-Fos on the promoter proximal region of its target genes in breast cancer and UGC [8,11] .…”
Section: Protein Expression Levels Of C-fos and C-jun In Different Hcmentioning
confidence: 99%
“…The c-Fos protein is transiently up-regulated in the early stages of hepatocarcinogenesis and then declines in the later stages of tumor progression. This temporary overexpression is needed for priming hepatocytes for migration and tissue invasion [15] . In contrast, the c-Jun protein is involved in tumor cell survival and apoptosis [16] .…”
Section: Introductionmentioning
confidence: 99%